Development of a new radiographic scoring system using digital image analysis. Issue 3 (March 1989) - Dacre, J E; Coppock, J S; Herbert, K E; Perrett, D; Huskisson, E C
Abstract : A scoring system using computerised analysis of digital stored images of knee radiographs has been developed. Measurement is based on the assessment of joint space size. It is sensitive, rapid, and reproducible. Plain radiographs are positioned on an acetate grid; a computer generated grid is superimposed on a digital image of the radiograph viewed on a closed circuit television monitor and the joint space measured automatically. Area and distance have been assessed; area measurements are more reproducible. Application of microcomputer based digital image analysis to radiological scoring systems is an important step in understanding the nature and progression of arthritis.